1986
DOI: 10.1177/004051758605601208
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical Model for the Lateral Compression of Woven Fabrics

Abstract: A mechanical model for the lateral compression of woven fabrics is derived from Van Wyk's compression law for fiber assemblies. The pressure ( P ) and thickness (v) relationship is P = a/ ( v -v')3. The parameter v' refers to the core of the fabric, which is incompressible over the pressure range 2-5000 gf/cm 2 . The parameter a refers to the compressible surface layers and is dependent on the mass of fibers in the surface layers and their orientation.A comparison is made of the results obtained with the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 10 publications
0
64
0
2
Order By: Relevance
“…Based upon these facts, the compaction process is taken as an important parameter of the manufacturing process (Robitaille and Gauvin, 1998). Extensive research has been done on the compaction behaviour of textiles (Chen and Chou, 1999;Chen et al, 2001;Chen et al, 2006;De Jong et al, 1986;Gutowski and Dillon, 1992;Latil et al, 2011;Nguyen et al, 2013;Pearce and Summerscales, 1995). Van Wyk (1946) was probably the first to treat the fibres under compression as a system of bending units.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon these facts, the compaction process is taken as an important parameter of the manufacturing process (Robitaille and Gauvin, 1998). Extensive research has been done on the compaction behaviour of textiles (Chen and Chou, 1999;Chen et al, 2001;Chen et al, 2006;De Jong et al, 1986;Gutowski and Dillon, 1992;Latil et al, 2011;Nguyen et al, 2013;Pearce and Summerscales, 1995). Van Wyk (1946) was probably the first to treat the fibres under compression as a system of bending units.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research work has been reported in the literature on the compaction behaviour of different fabrics [4][5][6][7][8][9][10][11][12][13][14][15]. Van Wyk [16] was probably one of the first researchers to treat the fibres under compression as a system of bending units.…”
Section: Introductionmentioning
confidence: 99%
“…Pressing and decatizing [4] leads to flattening of the compressive surface fabric layers. Therefore it is expected that finishing will reduce fabric compressibility and the compressive index and increase the linearity of compression.…”
Section: Compressional Propertiesmentioning
confidence: 99%